2023
DOI: 10.1128/aac.00577-23
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum GCN5 plays a key role in regulating artemisinin resistance-related stress responses

Amuza Byaruhanga Lucky,
Chengqi Wang,
Ahmad Rushdi Shakri
et al.

Abstract: Plasmodium falciparum causes the most severe malaria and is exposed to various environmental and physiological stresses in the human host. Given that GCN5 plays a critical role in regulating stress responses in model organisms, we aimed to elucidate PfGCN5’s function in stress responses in P. falciparum . The protein level of PfGCN5 was substantially induced under three stress conditions [heat shock, low glucose starvation, and dihydroartemisinin, the active metabolite of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…4 ). It has also recently been shown that PfGCN5, a histone acetyl transferase, is involved in the resistance of P. falciparum to artemisinins by increasing the unfold protein response pathway (UPR) and controls 300–400 genes involved in stress responses [ 112 , 113 ]. On this basis, it could be hypothesized that resistance to artemisinins in P. falciparum may also rely on epigenetic regulation.…”
Section: Plasmodium Epigenetic Effectors As a Source Of Ther...mentioning
confidence: 99%
“…4 ). It has also recently been shown that PfGCN5, a histone acetyl transferase, is involved in the resistance of P. falciparum to artemisinins by increasing the unfold protein response pathway (UPR) and controls 300–400 genes involved in stress responses [ 112 , 113 ]. On this basis, it could be hypothesized that resistance to artemisinins in P. falciparum may also rely on epigenetic regulation.…”
Section: Plasmodium Epigenetic Effectors As a Source Of Ther...mentioning
confidence: 99%
“…Blasticidin S resistance is connected with cytoadherence-linked asexual protein 3 (CLAG3), regulated by H3K9ac and H3K9me3 [ 326 ]. Recent studies have demonstrated that PfGCN5 plays a role in artemisinin resistance by enhancing the unfolded protein response (UPR) pathway and regulating 300–400 genes associated with stress responses [ 327 , 328 ]. The inhibition of P.f.…”
Section: Antimalarials and Protein Modificationsmentioning
confidence: 99%